Regioselectivity of enzymatic modification of poly(methyl acrylate) - Pranee Inprakhon (2018)
Enzymes are potentially useful catalysts for polymerization as well as modification of polymers. While lipases have been used previously for polymerization reactions, they have not been used for modification of polymers. In this report, lipases were used to determine regioselective modification of ester functions in a telomer of poly(methyl acrylate). The influence of chain length on the extent of transesterification of methyl acrylate telomers of over(D Pn, -) 6-50 was studied by examining the relationship between the extents of enzymic modification to other telomerization parameters. The regioselectivity was observed when the average over(D Pn, -) of telomers is in a range of 6-22. At a higher over(D Pn, -) (>22), however, the average number of reacting ester functions per telomer strongly deviated from the theoretically predicted value. This phenomenon was suspected as a result of steric hindrance caused by folding of longer telomer chains. To verify this hypothesis, acrylate telomers at a over(D Pn, -) ranging from 10 to 42 were synthesized using a shorter telogen, i.e., 2,2′-ethanedithiol. The transesterification of these telomers showed a deviation in a degree of conversion when over(D Pn, -) was greater than 10, possibly indicating the inhibition caused by steric hindrance. Therefore, regioselective modification of acrylic polymers, which is difficult to achieve by conventional chemical methods, may be accomplished enzymatically. © 2007 Elsevier B.V. All rights reserved.